Knowledge and interaction in on-line discussions in Spanish by advanced language learners. Issue 3 (19th May 2017) - McCabe, Anne
ABSTRACT: This article provides results of analysis of data collected from online Spanish-medium subject courses taught in Spanish by the same teacher to students whose first language is English. The students are at a high-intermediate to advanced level (B2-C1), and are enrolled at an American university in Madrid in courses centring on topics of Spanish language and language teaching. The teacher categorized the discussions as more or less successful, mainly depending on the amount of interaction perceived as taking place, but also on the participants' ability to express the vertical knowledge of the disciplinary concepts they are studying. The study reported on in this article uses functionally oriented models of evaluative language and of knowledge to analyse a "problematic" on-line discussion, along with two other discussions which serve as points of comparison. Quantitative results, in the form of descriptive statistics, are presented in order to underpin a qualitative discussion of where the difficulties lie in students' ability to create an interactive discussion about course knowledge, leading to some suggestions for setting up on-line discussion in content-based courses, especially for students studying through an additional language.